Berlin Takes It Easy — Brussels (Still) Does Not - Jens Boysen-Hogrefe (Wirtschaftsdienst)
Abstract Various ways exist to make use of public debt financing despite the existence of the debt brake. These are outlined in the recent coalition agreement, which indicates that the new government will go in this direction. Particularly, the accounting of federal special funds will change and the role of public enterprises will increase. Budget surveillance at the European level, however, uses alternative accounting that remains unaffected. German budgets will likely run up against the current European rules in the medium run. Thus, the new budget plans also hint at the readiness to renegotiate fiscal rules for the European Union.